Malik Bennabi and the Intellectual Problems of the Muslim Ummah - Fawzia Bariun (International Institute of Islamic Thought, 1992)
In the last several decades, Muslim and non-Muslim scholars have studied the causes of the Muslim ummah‘s decline. As thes scholars have different frames of reference and different political and cultural orientations, each group tends to view the issue according to its own understanding. However, the outcome of these studies are marred by major methadological defects that have made it impossible for the authors to move beyond a mere categorization of the multiple symptoms of that malady. Most non-Muslim scholars ascribe the Muslim world’s backwatdness to Islam. Such a conclusion mflects the confmntational stand of the West towards the Muslim world. Although the numerous writings on the subject have been called ”scientific” and "academic,” in reality they are mostly defensive and far fmm truly objective.’ Muslim thinkers and reformers, while admitting the fact of the ummah’s disintegration, have reached a different conclusion: Muslims, not Islam, have to change? Questions as to how and why this change should take place, as well as to who should undertake it, have remained largely incomplete and inconclusive for a variety of political and cultural circumstances. One major weakness was that most of the studies were descriptive, as opposed to analytical, in nature. If there were any analysis at all, it was mainly theoretical and superficial. The lack of freedom on different levels also interfered with ...